Measuring regional social inclusion performances in the EU: Looking for unity in diversity. (July 2019) - Rogge, Nicky; Self, Ryan
This study measures and benchmarks regional social inclusion performances in Europe using a composite index constructed on the basis of the commonly agreed sub-indicators of the Europe 2020 headline indicators. The multidimensional nature of these issues and the disparate social policy priorities of nations/regions in addressing them call for a reconciliatory performance evaluation framework, for which this article advocates the use of benefit-of-the-doubt (BoD) weighting. Based on the composite scores, leading and lagging regions in social inclusion are identified and the impact of regional contextual characteristics is examined. Overall results show that regions of Denmark and Sweden are consistently strong performers, while the Continental regions of Italy and Spain typically perform poorly. As to the poverty and social exclusion determinants, results show that low educational attainment and a high percentage of single-parent households relate negatively to regional social inclusion.